Optimizing Branding and Digital Marketing Through the Implementation of Augmented Reality (AR) Technology at Lukita Ceramic Studio - Yuniana Cahyaningrum; Rahayu Adi Prabowo; Asyifa’ Nur Istiqomah; Nikita Noviyanti; Dani Eka Ramdhani (Sah Publisher, 2026)
Lukita Ceramic Studio is a craft business that produces a variety of high-quality ceramic products. Despite its unique and attractive products, the studio faces significant challenges in branding and digital marketing. In the increasingly digital era, it is important for artisans to understand and utilize effective branding and digital marketing strategies to increase the visibility and competitiveness of their products. This activity aims to optimize Lukita Ceramic Studio's branding and digital marketing through the application of Augmented Reality (AR) technology. By using AR, the studio can introduce ceramic products interactively to consumers, providing a more immersive and engaging experience. This technology allows customers to view and interact with products in 3D, thereby increasing consumer appeal and trust in the products offered. This community service activity is designed to achieve three main objectives: (1) increasing the understanding of Lukita Ceramic Studio artisans about the importance of branding and digital marketing; (2) implementing AR technology to introduce products interactively; (3) increasing sales of Lukita Ceramic Studio products in the market. The methodology used in this program includes needs analysis, training on branding and digital marketing, AR application development, and evaluation of implementation results. It is hoped that through this program, Lukita Ceramic Studio can increase brand awareness, strengthen customer relationships, and drive product sales growth. This way, Lukita Ceramic Studio will not only be able to compete locally but also have the potential to expand into a broader market.